Crystal structure of ethyl 2-(2-{(1E)-[(E)2-(2-hydroxybenzylidene)hydrazin-1-ylidene]methyl}phenoxy)acetate. (February 2015) - Akkurt, Mehmet; Mague, Joel T.; Mohamed, Shaaban K.; Ahmede, Eman A.; Albayatif, Mustafa R.
No abstract available